2008
DOI: 10.1016/j.stem.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Formation of Polarized Cortical Tissues from ESCs and Its Active Manipulation by Extrinsic Signals

Abstract: Here, we demonstrate self-organized formation of apico-basally polarized cortical tissues from ESCs using an efficient three-dimensional aggregation culture (SFEBq culture). The generated cortical neurons are functional, transplantable, and capable of forming proper long-range connections in vivo and in vitro. The regional identity of the generated pallial tissues can be selectively controlled (into olfactory bulb, rostral and caudal cortices, hem, and choroid plexus) by secreted patterning factors such as Fgf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
1,200
5
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,286 publications
(1,293 citation statements)
references
References 42 publications
36
1,200
5
2
Order By: Relevance
“…An internal clock-like mechanism capable of counting the number of cell divisions that a progenitor cell goes through has also been proposed. Recently, it was shown that embryonic stem cells can be driven toward cells with dorsal telencephalic fate by blocking Shh-mediated signaling 30,31 . However, the amount of upper-layer neurons generated in these cultures was lower, suggesting that extrinsic factors that influence upper-layer cell fate were present.…”
Section: Discussionmentioning
confidence: 99%
“…An internal clock-like mechanism capable of counting the number of cell divisions that a progenitor cell goes through has also been proposed. Recently, it was shown that embryonic stem cells can be driven toward cells with dorsal telencephalic fate by blocking Shh-mediated signaling 30,31 . However, the amount of upper-layer neurons generated in these cultures was lower, suggesting that extrinsic factors that influence upper-layer cell fate were present.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the generation of the different neuronal subtypes found within the six distinct layers of the mammalian cortex from embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) has been established in adherent monolayer culture systems [1][2][3] and self-organized cultures with polarized cytoarchitecture [4]. With these types of approaches, the entire neurogenic process, from undifferentiated stem cells to terminally differentiated neurons, can be tracked in the defined conditions of a culture dish.…”
Section: Introductionmentioning
confidence: 99%
“…Independently Yoshiki Sasai's group explored directed differentiation of hPSCs after embryoid body (EB) formation, and developed a method known as the serum‐free culture of embryoid bodies after quick reaggregation (SEEBq) 25, 26. When specific neural inductive molecules were added, they generated polarized neural tissues 25, 26…”
Section: Human Neural Cultures: Historical Aspectsmentioning
confidence: 99%